The rapid and cost-effective capture and subsurface mineral storage of carbon and sulfur at the CarbFix2 site - Gunnarsson, I; Aradóttir, ES; Oelkers, EH; Clark, DE; Arnarson, MÞ; Sigfússon, B; Snæbjörnsdóttir, S; Matter, JM; Stute, M; Júlíusson, BM; Gíslason, SR (2018)
One of the main challenges of worldwide carbon capture and storage (CCS) efforts is its cost. As much as 90% of this cost stems from the capture of pure or nearly pure CO2 from exhaust streams. This cost can be lowered by capturing gas mixtures rather than pure CO2. Here we present a novel integrated carbon capture and storage technology, installed at the CarbFix2 storage site at Hellisheiði, Iceland that lowers considerably the cost and energy required at this site. The CarbFix2 site, located in deeper and hotter rocks than the original CarbFix site, permits the continuous injection of larger quantities of CO2 and H2S than the original site. The integrated process consists of soluble gas mixture capture in water followed by the direct injection of the resulting CO2-H2S-charged water into basaltic rock, where much of the dissolved carbon and sulfur are mineralized within months. This integrated method provides the safe, long-term storage of carbon dioxide and other acid gases at a cost of US $25/ton of the gas mixture at the CarbFix2 site and might provide the technology for lower CCS cost at other sites.